Peningkatan Kemampuan Kosakata Bahasa Inggris Melalui Penggunaan Media English Vocabulary Card - Muhammad Arief; Aditia Eska Wardana; Luthfi Hamdani Maula (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This research is motivated by the low mastery of students 'English vocabulary which can be seen from students' daily test results. The purpose of this study was to improve students' ability to master English vocabulary through media English Vocabulary Card fruit material and body parts. The research method used was Class Action Research with cycle models from Kemmis and Taggart. This research was conducted in two cycles equipped with the use of data collection tools in the form of test results and observation sheets. The learning process using English Vocabulary Card media has a good influence on students' mastery of English vocabulary. The results showed that the use of English Vocabulary Card media can improve students' mastery of English vocabulary. The increase can be seen from the average value of students' concept understanding tests at pre-action, which is 39.5 to 59.3 in the first cycle, so that there is an increase of 19.77 in capacity building. The average value of mastery of English in students in the first cycle was 59.3 to 76.02 in the second cycle, so that it increased by 16.70.